Is “Something Else” Needed Before Establishing a Family Council? The Role of Communication in Business Families - Rodríguez-García, María; González-Cruz, Tomás (European Journal of Family Business, 2024)
Establishing a family council can be beneficial for business families. However, determining the optimal circumstances to do so can be challenging. While some experts argue that a family council always provides long-term benefits, recent research on family councils suggests that there are certain prerequisites for successful family council implementation. This paper explores the nature of these prerequisites by examining communication dynamics within business families. Olson’s Circumplex Model is transferred from family therapy to the context of the family council by applying Habermas’s criteria for an ideal speech situation. Within this framework, a communication continuum on which to position business families is developed. This continuum is then applied to three Spanish business families. The findings suggest that a family council is functional only when minimum communication standards are met within the business family. Otherwise, the family council may have a minimal or even a negative impact. Families with an active family council should prioritise its use as a space for dialogue to enhance the business family’s functionality before tackling any other tasks or functions.